Early childhood educators' experience of an alternative physical education model. Issue 3 (3rd May 2016) - Tsangaridou, Niki; Genethliou, Nicholas
Abstract : Alternative instructional and curricular models are regarded as more comprehensive and suitable approaches to providing quality physical education (Kulinna 2008; Lund and Tannehill 2010; McKenzie and Kahan 2008; Metzler 2011; Quay and Peters 2008). The purpose of this study was to describe the impact of the Early Steps Physical Education Curriculum (ESPEC) on the professional lives of early educators and what impact they thought it had on their students' lives. This study, which was a part of a larger research project, was undertaken to deepen our knowledge of early childhood educators' perspectives and experiences of physical education. In purpose of this study, the participants were four Cypriot preschool teachers who were responsible for teaching physical education to those students participating in the Early Steps' Project and were trained in how to implement the ESPEC. Data were collected through formal interviews and analysed inductively via individual-case and cross-case analysis (Patton 2001). Results indicated that all participants enriched both their content and pedagogical knowledge. According to them, the implementation of the model facilitated their ability to design and deliver more meaningful experiences to their students. All four teachers pointed out that their participation in the programme helped their interpersonal relationships with the other early educators in their schools. According to these teachers, the ESPEC model benefited students. Findings indicated that the children's level of interest and enthusiasm during physical education lessons increased. In addition, the participants stated that during the implementation of the programme their students learned to communicate and cooperate with each other in a more meaningful way. Implications for preparing early childhood educators to teach quality physical education are discussed in light of the results.